Formação continuada de professores da educação do campo no município de Domingos Martins - ES - Nickel, Mônica (2016)
This study was developed in the research line Culture, Curriculum and Teacher Training, of the program of Graduate Studies in Education - PPGE - Centre of Education- CE of the Federal University of Espirito Santo - UFES and is linked to the Research Group (CNPQ ) Cultures, Partnerships and Rural Education. Investigates how the continuing education of Rural Education teachers, organized by the Research Centre contributes to the teaching practice in the city of Domingos Martins - ES. The worked theoretical references discuss dimensions of the practice of rural education, continuing education of teachers and about partnership (Freire 2005; 2011a and 2011b; Vazquez 2007; Arroyo 2007; Candau 2001 and 2003 and Foerste 2005). This research benefited from qualitative approaches in education (Lüdke and Andrew, 2006; Fichtner et al 2013). The Case Study favored our dialogue with the subjects of the training process the interview, document analysis and questionnaire for compiling the data. The survey results shows that continuing education of rural teachers currently is constituted in this city as a public policy, is developed dialectically and has contributed to the reflection and change in school practices.